Memaksimalkan Potensi Literasi Bahasa dan Budaya Jawa di Kecamatan Galur, Kabupaten Kulon Progo - Daru Winarti (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
Galur Subdistrict is an area that has abundant art and tradition potential and is in great demandby its people. Unfortunately, the art performances and traditions that are carried out only aim merelyto continue what have been done through generations. On the other hand, the inﬂux of modernarts has become a threat to preserving traditional culture, especially among young people who aresupposed to be the guardians of the traditions. Tis encourages Javanese Literature Study Programto carry out a community service program consisting of a series of training program as the StudyProgram’s concern and real action for cultural preservation.The training program is carried out through mentoring in motivating, counseling, education,discussion, and consultation. By using such mentoring techniques, it is expected that the result of theprogram will be optimum, namely raising public awareness to increase language literacy, knowledgeof literature, and the knowledge of the art performances they have. In turn, they will be able tomanage the performances as a professional art performance organizer in the region.The outcomes of the community service program comprise the increasing ability of participants inreading and writing simple texts using Javanese alphabet, participants’ ability to compose macapatsongs and sing them, the participants’ ability to write Javanese poems with the rinengga language,the participants’ ability create a series of dances and nursery rhymes to be performed, and theparticipants’ ability to become masters of ceremonies. In addition, three versions of Folklore aboutK.R.T Kertinegara are also collected